Branchless banking and profitability in the Indonesian Islamic banking industry - Mohammad Nur Rianto Al Arif; Uut Tri Cahyani (Faculty of Economics, Universitas Islam Indonesia, 2021)
Purpose – This study aims to examine the effect of branchless banking on the level of profitability in Islamic banks.Methodology – This study uses two Islamic banks that have implemented branchless banking (BRI Syariah and BTPN Syariah) and two Islamic banks that have not implemented this policy (BNI Syariah and Bukopin Syariah). This study uses regression analysis techniques with panel data. The model used in this study is the fixed effect model.Findings – This study shows that the branchless banking policy has a positive impact on profitability. This result implies that the implementation of branchless banking can improve the performance of Islamic banks in Indonesia. So, it is hoped that other Islamic banks can implement this branchless banking policy to overcome the limitations of their network. In addition, branchless banking can expand customer reach to areas that have not been served well by Islamic banks.Originality – Research on branchless banking in Islamic banks in Indonesia is still limited. There are only few studies comparing banks that have implemented branchless banking with banks that have not implemented this policy. Therefore, this research will contribute to a study that discusses branchless banking in Islamic banks in Indonesia, especially its impact on performance.